Reflections from design methodology, didactic strategies for project practice's teaching (ARQUISUR Revista, 2023)
This article constitutes a reflection on partial results of an ongoing doctoral thesis. We intend to assess the potential of developments in design methodology studies that were originally discussed at Portsmouth Symposium. These are reviewed and re-signified as alternatives for the construction of didactic strategies in teaching contemporary project practice. Being conceived as a particular dimension of teaching architecture, it constitutes a specific teaching object. Working with design methodology approaches allows us to build some tools for externalizing students’ questions that arise along the practice learning. This also brings out their positions on a project problem and the applied design decisions. This constitutes a series of concrete alternatives for teaching as regards the orientation/guidance to be provided in the development of the skills required for the project practice.
Keywords: architecture; cognition; education; educational strategies; professional training